Admission serum potassium levels and prognosis of vasospastic angina - Won-Woo Seo; Sang-Ho Jo; Sung Eun Kim; Hyun-Jin Kim; Seung Hwan Han; Kwan Yong Lee; Sung Ho Her; Min-Ho Lee; Seong-Sik Cho; Hack-Lyoung Kim; Sang Hong Baek (Scientific Reports, 2021)
Abstract Hypokalemia is a common electrolyte disturbance and is related to poor prognosis in patients with cardiovascular disease. However, the role of hypokalemia in patients with vasospastic angina (VSA) has not yet been studied. The present study enrolled 1454 patients diagnosed with VSA according to ergonovine provocation test results and available admission serum potassium data. The primary outcome was a composite of cardiac death, acute coronary syndrome, and new-onset life-threatening arrhythmia. Based on a hypokalemia definition as serum potassium concentration ≤ 3.5 mEq/L, the hypokalaemia group included 70 patients (4.8%). The median potassium levels were 3.4 mEq/L [interquartile range (IQR) 3.3–3.5] in the hypokalemia group and 4.1 mEq/L (IQR 3.9–4.3) in the no-hypokalemia group. The median follow-up duration was 764 days. Primary outcomes occurred in seven patients (10.0%) in the hypokalemia group and 51 patients (3.7%) in the no-hypokalemia group. The Kaplan–Meier analysis showed a higher cumulative incidence of primary outcomes in the hypokalemia group compared to that in the no-hypokalemia group (log-rank P = 0.014). Multivariate Cox regression analysis also showed that hypokalemia was an independent predictor of primary outcomes. In conclusion, hypokalemia at admission was associated with adverse clinical outcomes in VSA.